2019
DOI: 10.1136/bjophthalmol-2019-315255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopic maculopathy in the German population: results from the Gutenberg health study

Abstract: AimsTo determine the prevalence of myopic maculopathy in the general population in Germany and to analyse potential associations with ocular and systemic factors.DesignThe Gutenberg Health Study is a population-based study, including 15 010 participants aged 35–74 years.MethodsMyopic maculopathy was graded in phakic eyes with spherical equivalent ≤−6 D by assessing fundus photographs according to a recent international photographic classification system (META-PM). 801 eyes of 519 participants (mean age 51.0±0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
0
31
1
8
Order By: Relevance
“…2 Myopia is also a risk factor for various pathologies such as glaucoma, 3 cataract, 4 retinal detachment 5 and myopic maculopathy. 6 The latter has been reported to affect 0.5% of Germans aged 35-74 years 7 and 3.8% of older Singaporean adults (mean age 57.2 years). 8 In East Asia, myopia affects 80% to 90% of young adults.…”
Section: Introductionmentioning
confidence: 99%
“…2 Myopia is also a risk factor for various pathologies such as glaucoma, 3 cataract, 4 retinal detachment 5 and myopic maculopathy. 6 The latter has been reported to affect 0.5% of Germans aged 35-74 years 7 and 3.8% of older Singaporean adults (mean age 57.2 years). 8 In East Asia, myopia affects 80% to 90% of young adults.…”
Section: Introductionmentioning
confidence: 99%
“…10,29 Some systemic conditions, such as aging, gender, and hypertension, were also related to the development and progression of myopic maculopathy. [2][3][4]9,28,30,31 Clinically, we observed that some patients without significant anisometropia in both eyes had different MAM severities. In this situation, the elongated axial length was not the only contributing factor.…”
Section: Discussionmentioning
confidence: 55%
“…M yopic maculopathy is the leading cause of irreversible vision loss in this era, and its development and progression are strongly associated with aging and elongated axial length. [1][2][3][4][5][6][7][8][9] According to the newly proposed atrophy, traction, and neovascularization (ATN) classification system, myopic maculopathy can be classified into myopic atrophic maculopathy (MAM), myopic neovascular maculopathy (MNM), and myopic tractional maculopathy (MTM). 10 However, the mechanism underlying the development of MAM has not been fully elucidated.…”
mentioning
confidence: 99%
“…Since publication of the above data, four more reports of the relation between myopia level and the prevalence of myopic maculopathy have been published, [102][103][104][105] plus a fifth that does not contain sufficient categories. 106 All available studies are summarized in Table 3 and represent data from over 10,000 myopes.…”
Section: Myopia and The Risk Of Myopic Maculopathymentioning
confidence: 99%